Penerapan Mesin Purus Kayu Terintegrasi Sebagai Upaya Peningkatan Produktivitas Usaha Mebel - Kurniawan, Puthut Alfi Syahri; Barokah, Ramanda Ridho; Amar, Muhammad Iqbal; Meydiansyah, Dwi Yudha; Nanda, Iksan Riva; Wijayanto, Danar Susilo (DEDIKASI: Community Service Reports, 2023)
UD. Sunarso Mebel is a business engaged in the furniture industry with management, including the design stage, material search, sawing, shrinking, sorting, and assembly for the final product of furniture. Production process for mortise and tenon joint on UD. Sunarso Mebel identified problems that could have been more productive. UD. Sunarso Mebel uses conventional tools that are ineffective, efficient, and interfere with worker comfort. Therefore, the fabrication of integrated tenon wood machines is needed, about actual needs and conditions. The stages of this program include the formulation of the design, the tools' manufacturing stage, and the implementation stage. Using this integrated tenon wood machine increases the cutting speed of one wood couple to 10 seconds from the conventional method of 300 seconds. The stage of cutting one break that is needed is only one stage compared to the conventional method, which is three stages. The manufacturing capacity of furniture products has become nine times faster. Thus, these integrated tenon wood machines can increase the productivity of furniture products on UD. Sunarso Mebel. The ergonomics of integrated tenon wood machines are classified as low risk, so it is ready and safe for use.